Life-cycle assessment of a charging hub for electric trucks - Dahlberg, Gustav; Ramirez Rodriguez, Juan Pablo (My University, 2023)
This thesis aims to quantify the environmental impacts of constructing and operating a charging hub for electric trucks. The research questions are: (i) What are the life cycle environmental impacts of a charging hub?, and (ii) In what stage of the life cycle do the highest environmental impacts occur? A life cycle assessment (LCA) of the collaborating company’s charging hub is conducted, from cradle to grave. Four different scenarios are examined to evaluate the impacts: (i) a 7-year operational lifetime with low usage, (ii) a 7-year operational lifetime with high usage, (iii) a 21-year operational lifetime with low usage, and (iv) a 21-year operational lifetime with high usage. The LCA was performed using the openLCA software with the Ecoinvent 3.9.1 cutoff database. Inventory data was obtained directly from the company as well as adapted from literature. The impacts were evaluated for two impact categories: climate change using the global warming indicator, and mineral resource scarcity, using two different impact assessment methods – the surplus ore indicator and the crustal scarcity indicator. The results showed that the production and use phases are the most impacting phases in terms of climate change, with the highest production-related emissions owing to the production of electrical hardware, such as charging power units and the compact secondary substation. Furthermore, the production stage has the greatest impact for both the crustal scarcity and the surplus ore indicators in relation to mineral resource scarcity. A sensitivity analysis was performed by varying the amount of the printed circuit boards (PCBs). A decrease in PCBs showed a notable decrease in the overall environmental impacts of the hub.
Keywords: Life cycle assessment; charging station; environmental impacts; electric truck; fast charging